1991
DOI: 10.1159/000277058
|View full text |Cite
|
Sign up to set email alerts
|

Possible Selves across the Life Span

Abstract: Abstract. Possible selves have been defined as personalized representations of one's self in future states. In a study described in this article, respondents between the ages of 18 and 86 years were asked to describe their hoped-for and feared possible selves. Differences were found across age groups in the categories of possible selves mentioned most frequently and in respondents' evaluations of these possible selves. Moreover, respondents scoring low in life satisfaction generated different possible selves t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
494
1
12

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 578 publications
(527 citation statements)
references
References 21 publications
(26 reference statements)
20
494
1
12
Order By: Relevance
“…There is abundant evidence that young, middle-aged, and older adults are in different life stages and are faced with different life topics and life tasks. (Cross & Markus, 1991;Grob et al, 1999;Nurmi, 1992;Nurmi et al, 1992;Strough et al, 1996). We thus argue that our middle-aged respondents might be better able to view a goal in terms of its intrinsic and extrinsic components due to their respective standing in life.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…There is abundant evidence that young, middle-aged, and older adults are in different life stages and are faced with different life topics and life tasks. (Cross & Markus, 1991;Grob et al, 1999;Nurmi, 1992;Nurmi et al, 1992;Strough et al, 1996). We thus argue that our middle-aged respondents might be better able to view a goal in terms of its intrinsic and extrinsic components due to their respective standing in life.…”
Section: Discussionmentioning
confidence: 84%
“…Young, middle-aged, and older adults are typically in different phases of their lives, in which distinct topics are relevant or different tasks can or must be accomplished (e.g., getting started in work in young adulthood vs. retirement from work in later adulthood). Correspondingly, the goals people pursue generally reflect relevant life stage tasks (Cross & Markus, 1991;Grob, Little, & Wanner, 1999;Nurmi, 1992;Nurmi, Pulliainen, & Salmela-Aro, 1992;Strough, Berg, & Sansone, 1996). More specifically, goals related to education, partnership, friendships, and employment are more salient in young adulthood.…”
Section: A Life Span Perspective On Goals and Swbmentioning
confidence: 99%
“…Future selves (and other possible selves) are the elements of the self-concept that are likely to be most flexible and adaptable. Individuals have considerable freedom to define and redefine their future selves (Cross & Markus, 1991 The third explanatory process for the impact of salient Future Work Selves relates to research on future-oriented cognitive processes (e.g., Gilbert & Wilson, 2007;Suddendorf, 2006;Suddendorf & Corballis, 2007). Positive possible selves facilitate the identification of future requirements through mental simulation of the desired future (Kosslyn, 1987).…”
Section: The Motivational Role Of Future Work Self Saliencementioning
confidence: 99%
“…First, we expect positive Future Work Selves to be more prevalent and more salient than feared future selves because individuals have the desire to create and maintain positive identities at work (Ashforth, 2001). Previous research has found feared possible selves to be considerably less prevalent than hoped for possible selves (Cross & Markus, 1991;Markus & Nurius, 1986). Second, our conceptualization of Future Work Selves reflects the importance of positive reference values in self-regulation.…”
mentioning
confidence: 94%
“…The Nature and Correlates of Self-Esteem Trajectories in Late Life One major theme of personality and lifespan research has long been whether and how key aspects of the self are preserved when people are faced with major challenges of late life (Baltes & Carstensen, 1996;Brandtstädter & Greve, 1994;Cross & Markus, 1991;Freund & Smith, 1999;Orth, Trzesniewski, & Robins, 2010;Robins, Trzesniewski, Tracy, Gosling, & Potter, 2002;Troll & Skaff, 1997). One important indicator of the self is self-esteem, which revolves around a general evaluation and appraisal of one's worth (Leary & Baumeister, 2000;Orth et al, 2011).…”
mentioning
confidence: 99%